The Role of Consumers in Fostering Circular Economy in Indonesia - Pratiwi, Putu Yani; Handra, Tessa; Sutisna, Felix (STIE Malangkucecwara, 2024)
Consumers play an important role in transforming the economic system into a circular economy. Some literature highlighted that consumer demand has become an enabler for businesses to adopt circular practices. However, other literature argues that although consumers are aware of environmental sustainability issues, their adoption of circular products and services is still low, which is termed as an